Nutritional Quality of Pakchong, Zanzibar and Bio Grass Harvested at Different Ages - Ni Ketut Mardewi; I Wayan Agus Santika; Yan Tonga (Warmadewa University Press, 2023)
The study is intended to know the interaction between grass and cut age on the quality of grass, and knowing the type of grass and cut age best nutrients by the first - stage design method of grouping (R), a grass of the first factors (R), the grass of Zanzibar (R2), the biograss (R3), the second factor (U) of cut age: 50 days (U1), 60 days (U2), and 70 days (U3) with 3 deuteronomy. Studies have shown that there is real interaction (P <0.05) to very real (P < 0.01) between grass types and the age cut to nutrients such as water, ash, organic matter, rough protein, and rough fibers except that of coarse fat. The nutritional qualities of grass and the highest longevity of grasses and water content are produced from biograss grass at 50 days of age (R3U1), the highest ash content produced by zansibar grass with 60 days of grass And the highest concentration of crude fats from 50 days of living pakchong (R1U1) grass.